1989
DOI: 10.1099/0022-1317-70-1-173
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic Polyhedrosis Virus Classification by Electropherotype; Validation by Serological Analyses and Agarose Gel Electrophoresis

Abstract: SUMMARYSerological analyses of several different cytoplasmic polyhedrosis viruses (CPVs), including two type 1 CPVs from Bombyx mori, type 1 CPV from Dendrolimus spectabilis, type 12 CPV from Autographa gamma, type 2 CPV from Inachis io, type 5 CPV from Orgyia pseudotsugata and type 5 CPV from Heliothis armigera, demonstrated a close correlation between the antigenic properties of the polyhedrin or virus particle structural proteins and the genomic dsRNA electropherotypes. The dsRNAs of these viruses were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…Electrophoretic analysis in agarose gels is therefore not suitable for distinguishing between different AHSV serotypes. This is in agreement with results obtained for rotavirus (Pedley & McCrae, 1984) and other members of the Reoviridae family, with the exception of viruses belonging to the cytoplasmic polyhedrosis virus genus, which can be classified on the basis of distinctive agarose gel profiles (Mertens et al, 1989). Much of the variation in genomic profiles on polyacrylamide gels is due to differences in secondary structure of cognate genome segments rather than size differences.…”
Section: Discussionsupporting
confidence: 90%
“…Electrophoretic analysis in agarose gels is therefore not suitable for distinguishing between different AHSV serotypes. This is in agreement with results obtained for rotavirus (Pedley & McCrae, 1984) and other members of the Reoviridae family, with the exception of viruses belonging to the cytoplasmic polyhedrosis virus genus, which can be classified on the basis of distinctive agarose gel profiles (Mertens et al, 1989). Much of the variation in genomic profiles on polyacrylamide gels is due to differences in secondary structure of cognate genome segments rather than size differences.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, the apparent relatedness of the C-polyhedrin genes would have been underestimated. The results reported here for the intertypic differences, together with the intratypic conservation, support the current classification of CPV groups based upon the electrophoretic migration of the genomic dsRNA (Payne & Rivers, 1976;Payne et aL, 1977;Payne & Mertens 1983;Mertens et aL, 1989).…”
Section: Discussionsupporting
confidence: 86%
“…The viral genomes are composed of 10 discrete equimolar dsRNA segments. The electrophoretic separation of the genomic RNA has provided a means for classifying members of this group into 12 distinct classes (Payne & Rivers, 1976;Payne et al, 1977;Payne & Mertens, 1983;Mertens et al, 1989). Although the electrophoretic patterns of the genomic dsRNAs and virion-associated proteins are evidence for the diversity of this group of viruses, there are few reports on the sequence homologies of the various CPV types.…”
Section: Introductionmentioning
confidence: 99%
“…Different cypovirus "types" were initially identified on the basis of differences in the migration patterns of their genome segments during polyacrylamide gel electrophoresis, i.e., electropherotypes (22). Subsequent studies showed a good correlation between electropherotype and the grouping of strains on the basis of serological properties (18) or RNA cross-hybridization (17,20). It has recently been shown that, in addition to the RNA migration patterns, nucleotide sequences, for example, those of genome segment 10 (Seg-10; the polyhedrin gene), can be used to distinguish different Cypovirus species (20).…”
mentioning
confidence: 99%